2023
DOI: 10.1163/15685381-bja10131
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history drives the geographical distribution of dorsal patterns in the common wall lizard (Podarcis muralis)

Abstract: Melanin-based dorsal pattern polymorphisms are common in reptiles and generally evolve under the interaction between opposite selective pressures, notably thermal advantage in cold environments and background matching to avoid predation. When those pressures change over space and time, the relative frequencies of morphs can vary across the species range. However, no previous study has analysed the spatial patterns of variation of morphs under a phylogenetic perspective in addition to the adaptive responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study evaluates the variation in the chromatic patterns of a group of small lacertids that spread throughout the Mediterranean region and occupy diverse continental habitats and islands [ 22 ]. Intrageneric colouration patterns lack phylogenetic structure, in contrast to observations in some polytypic species, such as Podarcis muralis [ 23 ]. The analyses revealed that the development of abnormal chromatic patterns was negatively associated with the insular surface.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluates the variation in the chromatic patterns of a group of small lacertids that spread throughout the Mediterranean region and occupy diverse continental habitats and islands [ 22 ]. Intrageneric colouration patterns lack phylogenetic structure, in contrast to observations in some polytypic species, such as Podarcis muralis [ 23 ]. The analyses revealed that the development of abnormal chromatic patterns was negatively associated with the insular surface.…”
Section: Discussionmentioning
confidence: 99%